IT Maturity Level Analysis Using Framework COBIT 5 Work for Management Cyber Incident: Case Study of Company Z in ICT Field - Madiyaningsih, Inna; Ramli, Kalamullah (Universitas Wiralodra, 2023)
Based on the report security year 2022 from company Z in the ICT sector, it was found that on the report firewall security, 96% of level threat is level critical, and 4% is level high. Report email security is session domain 27.3%; Session limits 15.35 %; Forti Guard AntiSpam-IP 3.11%, and the rest is receipt verification; directory filter and access control relay denied. With the challenge of current cyber-attacks, precious data assets need analysis to measure the the level of IT maturity that can ensure stakeholders' interest and maximize benefits and opportunities through technology information. We overcome limitations by analyzing IT maturity using COBIT 5. Research focused only on the APO13 and DSS05 process domains. A study was done to identify the problems based on results observation, checking, and use of a questionnaire in a direct manner. Measurement is done through method evaluation self and interviews deep with the IT team and all power expert who has COBIT certification 5. Analysis results show that the measurement level for the APO13 domain is 3, and for DSS05 is level 2. These results still need to be below the set level 4 target management; therefore, building a framework to monitor, track, and record security data in real time is necessary. With the build framework, Work can help lower the threat level from a critical level to a high level and increase the COBIT Maturity Level to APO13 and DSS05 according to organizational targets.